Effect Of Copper On Passivity And Corrosionbehavior Of Fe-xc-5cu Alloy - Ferhat, M.; Benchettara, A.; Amara, S. E. (University of Eloued جامعة الوادي, 2014)
The correlation between corrosion behavior rate of annealed Fe-xC-5Cu alloys and their microstructure and phase composition is presented. The metallurgical analyses, including, X-Ray diffraction (XRD), the scanning electron microscopy (SEM) with energy dispersive analysis (EDX), and induction hardening characterization are conducted to study the Fe-C-Cu alloys.Corrosion parameters in H2SO4 1N solution have been established by carrying out electrochemical studies such as potentiodynamic (Tafel polarization and linear polarization, LP) and electrochemical impedance spectroscopy (EIS).The coupled effect copper/microstructure is discussed. Alloying Cu showed a beneficial effecton hypoeutectoid steel and harmful effect on hypereutectoid steel. The improved corrosion resistance is related to cementite morphology and by a copper dissolution/re-deposition process.
Articale in Journal of fundamental and Applied Sciences Vol. 06 N. 01
Keywords: Corrosion;Copper;cementite;EIS; Passivation; Hardness.